THE STREET LAW PROGRAM AS A TYPE OF ALTERNATIVE EDUCATION AND A MEANS OF RAISING LEGAL AWARENESS IN SOCIETY - Mkrtchyan, Satenik; Vardanyan, Knarik (Bulletin of Yerevan University C: Jurisprudence, 2026)
This article explores the Street Law program implemented by the Legal Clinic as a compelling model of alternative legal education and an effective instrument for raising public legal awareness. It delves into the origins and development of non-formal education, shedding light on its unique characteristics and the methods of its application—particularly within the framework of clinical legal education. Special attention is given to the dual educational effect of the program: on one hand, it equips law students with hands-on, practice-oriented training, and on the other, it helps enhance legal literacy among diverse social groups that may lack access to formal legal education. Grounded in both theoretical insights and practical experiences, the article argues that Street Law serves not merely as an innovative pedagogical tool, but also as a powerful vehicle for advancing the rule of law, nurturing civic engagement, and cultivating a legally informed society.